Analysis of Financial Ratio That Affecting Total Financing of Bank Umum Syariah In Indonesia - Ulfa, Zerlinda Tharifah; Purwanto, Purwanto (MALIA: Journal of Islamic Banking and Finance, 2020)
This study aimed to analyze the factors that influence the Total Financing of Bank Umum Syariah (BUS) in Indonesia. Islamic banking system in Indonesia was developed within the framework of the dual banking system to give alternatives for more complete banking services to the people of Indonesia. Islamic banking in Indonesia has grown rapidly every year, but it can not be denied the role of Islamic banking in the economy is still relatively small compared with conventional banking. The amount of total financing is only about 5,56% of the banking total credit. It can be seen also in the proportion of assets Islamic banking to national banking assets that only 4.8% and 18.75% of the total national banking accounts. The research data is taken from the financial reports of 10 of Islamic banks in Indonesia. The method used is a quantitative method and multiple regression analysis, proceed using SPSS to test normality, multicollinearity, heteroscedasticity and autocorrelation. The result of this research showed that the Capital Adequacy ratio(CAR), Non-Performing Financing (NPF), and Operating Expense Operating Income ratio (OEOI) had a significant effect on total financing. Meanwhile, Return on Asset (ROA) and Financing to Deposit Ratio (FDR) had no significant effect on the total financing of Bank Umum Syariah. Adjusted R Square value is 0.239 or 23,9%. This value shows that the percentage of the contribution of independent variables on total financing is 23.9 %.  The remaining percentages are due to other variables excluded in this model.